A 52-year-old-male patient with metastatic non-small-cell lung cancer and recurrent venous thromboembolism in unusual sites despite anticoagulation. (17th September 2013) - Matikas, Alexios; Vardakis, Nikolaos; Souglakos, John; Georgoulias, Vassilios
Abstract : The link between cancer and venous thromboembolism is well known, with an annual incidence rate of venous thromboembolism between 0.5% and 20% depending on the primary site and background risk factors. Current guidelines suggest treatment with low-molecular-weight heparin over oral vitamin K antagonists. However, data regarding the management of recurrent venous thromboembolism when the patient is under treatment with anticoagulants are sparse. In this article we present a patient with multiple thromboembolic events in unusual sites despite anticoagulant treatment and we discuss the management options.